Evaluasi Kepatuhan terhadap Regulasi Pengelolaan Limbah Medis Berbahaya dan Beracun (B3) di Rumah Sakit dr. Hasri Ainun Habibie Parepare - Laupe Rado, Muhammad Yusuf; Amir, Rahmi; Herlina, Herlina; Haniarti, Haniarti; Thasim, Sukma (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Three types of hazardous and toxic waste are separated in hospitals: home garbage, non-infected medical waste, and infectious medical waste. In addition to polluting the environment, improper management of this waste can endanger the health of patients, healthcare workers, and the local population. There are still a number of issues with medical waste management at Dr. Hasri Ainun Habibie Hospital, especially with regard to the collection, sorting, and storage of hazardous waste. The objectives of this study are to assess the hospital's hazardous waste management system, pinpoint its problems, and develop tactical suggestions to increase management efficacy. With 14 respondents, the study employed a descriptive qualitative methodology. The MAXQDA application was used for data processing and analysis in order to produce reliable and organized results. The results of the study show that Dr. Hasri Ainun Habibie Hospital's hazardous waste management system still need work, especially in terms of standard operating procedures (SOPs) and regulatory comprehension. Sorting, storing, transporting, and disposing of garbage present the biggest obstacles. Thus, the employment of technology innovation, educational initiatives, and staff skill development are all included in the suggested strategic proposals. It is anticipated that this study will serve as a guide for improving hospital waste management systems. Keywords: B3 Waste, SOP, Hospital